Occurrence of Vanadium in Belgian and European Alluvial Soils - V. Cappuyns; E. Slabbinck (Applied and Environmental Soil Science)
Vanadium (V) is a naturally occurring trace element, but total concentrations in soils and sediments are also dependent on the parent material and might be influenced by anthropogenic activities (e.g., steel industry). Despite the fact that threshold values for V in soils and/or sediments exist in various European countries, in Belgium, V is not taken into account when the environmental quality of soils and sediments has to be evaluated, despite the existence of several (diffuse) sources for V. In the first part of the study, the occurrence of V alluvial soils in Belgium was compared with V concentrations in alluvial soils (floodplain soils) across Europe. By analysis of both the Belgian and European data, the relationship between physicochemical soil characteristics and total V concentrations was quantified and some areas polluted with V were detected. A regression equation, in which V concentrations in alluvial soils were expressed as a function of major element composition, was proposed for the Belgian and European data. Additionally, single extractions with CaCl2 (0.01 mol L-1) and ammonium-EDTA (0.05 mol L-1) were used to estimate short- and long-term mobility of V in the alluvial soils.